1995
DOI: 10.1128/jcm.33.11.2876-2880.1995
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ear fluid isolates of Alloiococcus otitidis from patients with recurrent otitis media

Abstract: Nineteen isolates of Alloiococcus otitidis from ear fluid samples collected by tympanostomy from patients at four geographic locations were identified by phenotypic characterization and genetic relatedness. Initial growth of A. otitidis isolates occurred after 3 days at 37؇C on brain heart infusion (BHI) agar with 5% rabbit blood. Heavy growth occurred in BHI broth supplemented with 0.07% lecithin and 0.5% Tween 80 after 4 days of incubation. The isolates were gram-positive cocci that divided on an irregular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 15 publications
0
24
1
1
Order By: Relevance
“…These plates were then incubated for a further 7 days before being discarding as negative. Previous authors reported sparse growth using this broth after 3 days of incubation (Bosley et al, 1995) and positive results but an unspecified incubation time for this broth medium (Faden & Dryja, 1989).…”
Section: Culture Methodsmentioning
confidence: 71%
See 3 more Smart Citations
“…These plates were then incubated for a further 7 days before being discarding as negative. Previous authors reported sparse growth using this broth after 3 days of incubation (Bosley et al, 1995) and positive results but an unspecified incubation time for this broth medium (Faden & Dryja, 1989).…”
Section: Culture Methodsmentioning
confidence: 71%
“…All media were incubated for a total of 7 days in 7.5% (v/v) carbon dioxide at 35 1C. The incubation period was longer than those previously described for isola-tion of A. otitidis: 4 days (Bosley et al, 1995), 5 days (Faden & Dryja, 1989), 5 days (Stroman et al, 2001).…”
Section: Culture Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a recent study using PCR for the detection of microbes, A. otitidis was found in over 40% of child OME cases (3,11) and was more frequently detected than other common pathogens of otitis media (11). There have been reports of the isolation of Alloiococcus otitidis strains which were resistant to both erythromycin and trimethoprimsulfamethoxazole and relatively resistant to beta-lac- tams (4). Therefore, this new bacterial species, A. otitidis, should be examined to determine whether or not it has a pathogenetic role in the occurrence of otitis media.…”
mentioning
confidence: 99%